(untitled) (Global Journals of Research in Engineering, 2012)
Investigations on the bioconcentration of heavy metals Cu Ni Fe Co Mn Cr and Zn were observed in Channa punctatus The results revealed that heavy metals available in water were in the order Fe Mn Zn Co Ni Cu Cr The accumulation was also observed in tissues such as gills liver kidney muscle and integument Their pattern of accumulation in muscle was Fe Zn Mn Cu Cr Ni Co All the heavy metals showed maximum concentration and persistence in gills with the exception of Cu and Co which showed maximum accumulation in liver and muscle respectively Fe was the most abundant metal in the water as well as in the fish tissues Significant P 0 01 relations were observed among the metal accumulations in different organs of the fish The concentration observed was far exceeding the recommended limits of FAO WHO